The English Teachers’ Instructional Strategies to Assist Students to Meet the Minimum Criterion of Mastery Learning - Haryanto, Jessica Febrina; Ngadiman, Agustinus (Universitas PGRI Adi Buana Surabaya, 2018)
This article uncovered the instructional strategies used by Junior High English teacher to assist students to achieve the determined Minimum Criterion of Mastery Learning (MCML) or KKM (Kriteria Kompetensi Minimal). The subjects of the study were 4 English Teachers of Junior High Schools and Senior High Schools in Surabaya. They were assumed to have had enough experiences in teaching EFL to the students. The main instrument of the study was a semi structured questionnaire. There were ten strategies used by English Teachers of Junior High Schools and Senior High Schools to assist their students to meet the Minimum Criterion of Mastery Learning. They are (1) Conducting short review, (2) Teaching step-by-step, (3) Giving a large number of questions, (4) Giving a large number of questions, (5) Guiding the students’ practices, (6) Checking the students’ understanding, (7) Obtaining high success rate. (8) Providing scaffolds for difficult tasks, (9) Assessing independent practices, and (10) Conducting weekly and monthly review. Keywords: Minimum Criterion of Mastery Learning (MCML), strategies